Mengungkap Dinamika Penentuan Tarif Jasa Content Writer Di Kota Palu: Analisis Kualitatif Berbasis Akuntansi Manajemen - Iftitah Azzahra; Sugianto; Ernawaty Usman; Abdul Kahar (P3M Politeknik Negeri Banjarmasin, 2025)
This study aims to explore the dynamics of service pricing among content writers in Palu City from a management accounting perspective. A qualitative approach was employed to gain an in-depth understanding of the social and economic phenomena surrounding the content writing service industry. Data were collected through in-depth interviews with content writing practitioners based in Palu. The findings reveal that pricing decisions are influenced by relational dimensions such as feelings of discomfort or reluctance when dealing with friends, empathy toward clients’ financial conditions, and the general lack of appreciation for creative processes. In addition, work experience plays a central role in shaping value perception and price legitimacy. These findings underscore the significance of relational approaches in understanding pricing structures within the creative service sector and highlight the need to integrate social values into management accounting practices. The absence of standardized pricing leads to high variability in service rates, posing challenges particularly for novice writers in determining fair compensation. From a management accounting standpoint, rational pricing requires an understanding of cost structures, profit margin calculations, and the evaluation of efficiency and competitiveness. The study concludes that implementing cost-based pricing and cost behavior analysis is highly relevant to enhance transparency and fairness in service fee structures. These insights are expected to serve as a foundation for developing more systematic pricing guidelines and promoting greater professionalism within the local creative industry, particularly in Palu City.